Offshoring software development: Case of Indian firms in Finland - Jyrki Ali-Yrkkö; Monika Jain (The Research Institute of the Finnish Economy (ETLA), 2005)
This exploratory study examines outsourcing and offshoring of software development by analysing Indian companies in Finland. Based on qualitative data our results support the view that offshore outsourcing decisions are usually cost-driven. Another important motive has been the availability of software skills. To speed up the product development, some firms have outsourced maintenance and sustenance of existing products, which, in turn, has enabled the company to focus its in-house R&D resources on the development of next generation products and technology. In the future, offshoring software development will probably increase not only through outsourcing, but also through in-house operations. In addition to India, other potential locations include Russia and Eastern Europe.
Keywords: 330; Software; R&D; research and development; offshoring; outsourcing; Programmierung; Industrielle Forschung; Softwareindustrie; Outsourcing; Finnland; Indisch